2007
DOI: 10.1128/mcb.01485-06
|View full text |Cite
|
Sign up to set email alerts
|

Role for Furin in Tumor Necrosis Factor Alpha-Induced Activation of the Matrix Metalloproteinase/Sphingolipid Mitogenic Pathway

Abstract: Neutral sphingomyelinase (nSMase), the initial enzyme of the sphingolipid signaling pathway, is thought to play a key role in cellular responses to tumor necrosis factor alpha (TNF-␣), such as inflammation, proliferation, and apoptosis. The mechanism of TNF-␣-induced nSMase activation is only partly understood. Using biochemical, molecular, and pharmacological approaches, we found that nSMase activation triggered by TNF-␣ is required for TNF-␣-induced proliferation and in turn requires a proteolytic cascade in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
70
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 59 publications
4
70
0
3
Order By: Relevance
“…Many studies have also observed that MMPs, and in particular MMP-2 and MMP-9, are expressed in stromal cells and inflammatory cells around tumors (72). These findings suggest the importance of these proteases in the pathogenesis of cancer.…”
Section: Mmps In Uterine Cervical Neoplasmmentioning
confidence: 74%
“…Many studies have also observed that MMPs, and in particular MMP-2 and MMP-9, are expressed in stromal cells and inflammatory cells around tumors (72). These findings suggest the importance of these proteases in the pathogenesis of cancer.…”
Section: Mmps In Uterine Cervical Neoplasmmentioning
confidence: 74%
“…L-аргинил-треонил-лизил-L-аргинина (Pyr-ArgThe-Lys-Arg-MCA) [20]. Опытная проба объёмом 500 мкл содержит 5-100 мкл образца (5-10 мкг белка), Pyr-Arg-The-Lys-Arg-MCA (в конечной концентрации 4´10 -5 М).…”
Section: мт1-ммп и ее эндогенные регуляторы при карциноме шейки маткиunclassified
“…ТИМПы обладают "цитокино-подобной" активностью и могут принимать участие в регуляции таких процессов как апоптоз и клеточный рост [4,[7][8][9]. Активация про-МТ1-ММП осуществляется внутриклеточно в аппарате Гольджи с помощью сериновой протеиназы -фурина [10].…”
Section: Introductionunclassified
“…Prior to the cloning of nSMase2, it was first identified as a confluent cell-associated gene in rat 3Y1 cells (14) and was subsequently implicated in confluence-induced G 0 /G 1 cell cycle arrest in MCF-7 breast cancer cells (15). Many studies have reported activation of nSMase2 by tumor necrosis factor in a variety of cell types including smooth muscle cells, HUVECs and A549 cells, although regulation of nSMase2 appears to be cell type dependent with protein kinase C-delta and p38 MAPK involved in A549 cells (16,17), and matrix metalloproteinases, furin and integrins involved in smooth muscle cells (18). In addition, nSMase2 was implicated in aging-associated inflammation, particularly in the response to interleukin-1␤ (19).…”
mentioning
confidence: 99%